Testosterone protects from metabolic syndrome-associated prostate inflammation: an experimental study in rabbit - Vignozzi, Linda; Morelli, Annamaria; Sarchielli, Erica; Comeglio, Paolo; Filippi, Sandra; Cellai, Ilaria; Maneschi, Elena; Serni, Sergio; Gacci, Mauro; Carini, Marco; Piccinni, Marie-Pierre; Saad, Farid; et al. (Journal of endocrinology, 2012)
Metabolic syndrome (MetS) and benign prostatic hyperplasia (BPH)/lower urinary tract symptoms (LUTS) are often associated. One of their common denominators is hypogonadism. However, testosterone supplementation is limited by concerns for potential prostatic side effects. The objective was to determine whether MetS-associated prostate alterations are prevented by testosterone supplementation. We used a previously described animal model of MetS, obtained by feeding male rabbits a high-fat diet (HFD) for 12 weeks. Subsets of HFD rabbits were treated with testosterone or with the farnesoid X receptor agonist INT-747. Rabbits fed a standard diet were used as controls. HFD-animals develop hypogonadism and all the MetS features: hyperglycemia, glucose intolerance, dyslipidemia, hypertension, and visceral obesity. In addition, HFD-animals show a prostate inflammation. Immunohistochemical analysis demonstrated that HFD-induced prostate fibrosis, hypoxia, and inflammation. The mRNA expression of several proinflammatory (IL8, IL6, IL1β, and TNFα), T lymphocyte (CD4, CD8, Tbet, Gata3, and ROR γt), macrophage (TLR2, TLR4, and STAMP2), neutrophil (lactoferrin), inflammation (COX2 and RAGE), and fibrosis/myofibroblast activation (TGFβ, SM22α, αSMA, RhoA, and ROCK1/ROCK2) markers was significantly increased in HFD prostate. Testosterone, as well as INT-747, treatment prevented some MetS features, although only testosterone normalized all the HFD-induced prostate alterations. Interestingly, the ratio between testosterone and estradiol plasma level retains a significant, negative, association with all the fibrosis and the majority of inflammatory markers analyzed. These data highlight that testosterone protects rabbit prostate from MetS-induced prostatic hypoxia, fibrosis, and inflammation, which can play a role toward the development/progression of BPH/LUTS.